Body Composition in Javanese Adult: Some Anthropometric Dimensions Related to Body Fat - Janatin Hastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Body composition is an integral component of entirely health and physical fitness. Measurement of fat component in assessing body composition is necessary on account of its relation to several health risks. Some anthropometric measurements such as waist to hip ratio (WHR), waist and hip circumferences, skinfold thickness, and sagittal abdominal diameter are demonstrated to be valuable for evaluating body composition, and further for identifying some health risk factors. Objectives: This study is addressed to know body composition and some anthropometric measurements related to percent body fat in Javanese adults living in Yogyakarta province. Methods: As many as 201 (98 males and 103 females) Javanese adults living in Yogyakarta province, aged 18 to 65 years were entrolled in this study. Measurements of body weight, height, waist, abdominal, and hip circumferences, sagittal abdominal diameter, and total skinfold thickness of triceps, biceps, subscapular, suprailiac were performed on the subjects. Body composition was assessed based on those measurements included percent body fat, body density, and skeletal muscle mass. Body mass index and waist-to-hip ratio were determined and categorized. The data then were analysed using independent Hest, Pearson correlation of product moment, linear regression, and chi-square test. Results: The result indicated that in a general sense, Javanese adults in Yogyakarta province had thin to medium body constitution and risk factor categorized of low to medium risk for males and medium to high risk for females. Javanese adult males were considerably heavier, taller, had greater means of body density, WHR, and muscle mass. By contrast, Javanese adult females were significantly higher in BMI, percentage of BF, and hip circumference. Statistically, there is no significant difference in total skinfold, abdominal circumference, and SAD, however, females indicated to a certain greater than the males. In the same manner, males had larger waist circumference. Conclusions: All of anthropometric dimensions including skinfold thickness, body density, waist circumference, abdominal circumference, WHR, sagittal abdominal diameter, and muscle mass are strongly correlated with body composition assessed with BMI and % BF. However, associations with BMI are fairly better than those of with percentage of BF. Among those measurements WHR showed the weakest correlation. There was also a different tendency in the power of correlation between anthropometric dimension with BMI and percentage of BF in males and females. Yet, all the measurements were supposed to be performed to incorporate evaluation on human body composition. Key words: body composition - Javanese adults - anthropometric measurements - percentage of body fat.